Gambaran Perilaku Picky Eater, Pola Makan Dan Status Gizi Anak Autis Di Slb Negeri Semarang - Rahayu, Sasi; , Elida Soviana, S.Gz., M.Gizi; , Ruli Sudaryanto, SST.GZ (2016)
Introduction: Autism is a developmental disorder which characteristed by defficulties in verbal and non verbal comunication, social interaction and severe behavioral disorder. Children with higher malnutrition due to several factors. They are known to have a strict diet, picky eater behaviour such a afraid to try new food and chewing problem, limited food intake lack of nutritional knowledge of the parents and side effect of the drugs they consumed. Objective: To describe picky eater behaviour, dietary intake and nutritional status of children with autism. Research methods: This is an observasonal study with cross-sectional. A total of 30 subjects were selected by proposional random sampling that meet the inclusion and eksklusion criteria. Data of picky eater behaviour and dietary intake were obtained by interview using questionaire and nutritional status data were calculated by measuring height and weight. Results: All of the subject (100%) have a picky eater behaviour. Most of them (76,7%) experienced a bad eating habit. 30% of the subject were undernutrition, 46,7% of the subject were normal and 23,3% were overnutrition. Conclusion: Most of the subject still consuming high gluten and casein food and have picky eater behaviour. Therefore, it is necessary to increase knowledge about autism and picky eater behaviour.